Analisa Pengaruh Kompetisi Pasar Produk, Ukuran Perusahaan, Leverage, Profitabilitas, Property, Plant And Equipment (PPE) dan Pertumbuhan Penjualan Terhadap Tax Avoidance Pada Perusahaan Manufaktur di Indonesia - Vidya Ramarusad; Desi Handayani; Ulfi Maryati (Jurnal Akuntansi Keuangan dan Bisnis, 2021)
This study aims to analyze the effect of product market competition, firm size, leverage, profitability, plant, property and equipment (PPE) and sales growth on tax avoidance. The object of this research is a manufacturing company listed on the Indonesia Stock Exchange in the period 2015 to 2019. The research method used is quantitative methods. The sample was determined based on the purposive sampling method. Overall, there were 134 companies to be sampled that met the criteria and passed the classic assumption test problems. The sources used are secondary data in the form of financial reports and annual reports obtained from the Indonesia Stock Exchange website (www.idx.co.id). The data processing program uses the Statistical Product and Service Solution (SPSS) version 25 program. The method of analysis used in this study is multiple linear regression. Based on the results of multiple linear analysis with a significance level of 5%, the results of this study conclude that the variables of product market competition, leverage, plant, property and equipment (PPE) and sales growth have no effect on tax avoidance, company size has a positive effect on tax avoidance, profitability has an effect. negative towards tax avoidance.